Transcriptional, Electrophysiological, and Metabolic Characterizations of hESC-Derived First and Second Heart Fields Demonstrate a Potential Role of TBX5 in Cardiomyocyte Maturation - Pezhouman, Arash; Nguyen, Ngoc B.; Sercel, Alexander J.; Nguyen, Thang L.; Daraei, Ali; Sabri, Shan; Chapski, Douglas J.; Zheng, Melton; Patananan, Alexander N.; Ernst, Jason; Plath, Kathrin; Vondriska, Thomas M.; et al. (Frontiers in Cell and Developmental Biology, 2021)
Background: Human embryonic stem cell-derived cardiomyocytes (hESC-CMs) can be used as a source for cell delivery to remuscularize the heart after MI. Despite their therapeutic potential, the emergence of ventricular arrhythmias has limited their application. We previously developed a double reporter hESC line to isolate first heart field (FHF: TBX5+NKX2-5+) and second heart field (SHF: TBX5-NKX2-5+) CMs. Herein, we explore the role of TBX5 and its effects on underlying gene regulatory networks driving phenotypical and functional differences between these two populations. Methods: We used a combination of tools and techniques for rapid and unsupervised profiling of FHF and SHF populations at the transcriptional, translational, and functional level including single cell RNA (scRNA) and bulk RNA sequencing, atomic force and quantitative phase microscopy, respirometry, and electrophysiology. Results: Gene ontology analysis revealed three biological processes attributed to TBX5 expression: sarcomeric structure, oxidative phosphorylation, and calcium ion handling. Interestingly, migratory pathways were enriched in SHF population. SHF-like CMs display less sarcomeric organization compared to FHF-like CMs, despite prolonged in vitro culture. Atomic force and quantitative phase microscopy showed increased cellular stiffness and decreased mass distribution over time in FHF compared to SHF populations, respectively. Electrophysiological studies showed longer plateau in action potentials recorded from FHF-like CMs, consistent with their increased expression of calcium handling genes. Interestingly, both populations showed nearly identical respiratory profiles with the only significant functional difference being higher ATP generation-linked oxygen consumption rate in FHF-like CMs. Our findings suggest that FHF-like CMs display more mature features given their enhanced sarcomeric alignment, calcium handling, and decreased migratory characteristics. Finally, pseudotime analyses revealed a closer association of the FHF population to human fetal CMs along the developmental trajectory. Conclusion: Our studies reveal that distinguishing FHF and SHF populations based on TBX5 expression leads to a significant impact on their downstream functional properties. FHF CMs display more mature characteristics such as enhanced sarcomeric organization and improved calcium handling, with closer positioning along the differentiation trajectory to human fetal hearts. These data suggest that the FHF CMs may be a more suitable candidate for cardiac regeneration.